(1041) Urbanization and Economic Development التوسع الحضري والتنمية الاقتصادية - Mohamed H. Fag El Nour. (معهد التخطيط القومى, 2020)
The process of urbanization is now more rapid and massive than it have ever been before. This is especially true for the greater part of developing world where urbanization is over leaping. The rural urban migration of hundreds of millions of people in these still shiefly agrarian economies is tremendously affecting the life of humanity. The unprecedented rates of overall population growth are helping to swell the populations of individual cities in such a way that were hardly conceived half of century